A functional trait framework for integrating nitrogen‐fixing cover crops into short‐rotation woody crop systems. Issue 5 (19th March 2023) - Ferreira, Gabriel W. D.; Aubrey, Doug P.
Abstract: Developing approaches to simultaneously maximize short‐rotation woody crop (SRWC) productivity while minimizing footprints associated with intensive management is imperative to profitable and sustainable bioenergy production systems. Intercropping nitrogen (N)‐fixing cover crops in SRWC systems is an overlooked approach to sustainably intensify SRWC production by increasing N availability using less environmentally costly inputs. Here, we discuss how functional traits (e.g., seasonal activity, lifespan, leaf habit, soil exploration) of cover crops and SRWCs may interact through space and time influencing access to light, water, and nutrients to provide a framework for successful integration of cover crops into SRWCs. Next, we summarize the literature on intercropping forest plantations with N‐fixing cover crops to identity research gaps and outline future research needs and opportunities. And then, using empirical N demand and productivity data from SRWCs and cover crop N inputs from the literature, we illustrate how SRWC leaf habit (conifer evergreens and deciduous hardwoods) would influence successful integration of cover crops and potential N fixation. We estimate that integrating cover crops into SRWCs could supply 27% and 72% of the N demand across a 10‐year rotation for an evergreen and a deciduous hardwood, respectively. These figures suggest these integrated SRWC systems may approach a virtual minimal external N input when other biogeochemical cycles are considered. The guiding principles presented here are grounded in ecological theory and provide a framework for sustainable intensification of forest production. Abstract : Our study discussed the potential of integrating nitrogen (N)‐fixing cover crops into short‐rotation woody crop (SRWC) systems as an alternative for ecological intensification of bioenergy production systems. Using ecological theory and numerical simulations, we explored how functional traits (e.g., seasonal activity, lifespan, leaf habit, soil exploration) of cover crops and SRWCs can influence competition for resources in space and time to provide a framework for successful integration of cover crops into SRWCs. Our simulations suggest integrated SRWC systems increase whole‐system N cycling potential and reduce external N demand, ultimately maximizing SRWC productivity while reducing greenhouse gas emissions and N pollution.